A deepening understanding of animal culture suggests lessons for conservation. Issue 1949 (21st April 2021) - Brakes, Philippa; Carroll, Emma L.; Dall, Sasha R. X.; Keith, Sally A.; McGregor, Peter K.; Mesnick, Sarah L.; Noad, Michael J.; Rendell, Luke; Robbins, Martha M.; Rutz, Christian; Thornton, Alex; Whiten, Andrew; et al.
Abstract : A key goal of conservation is to protect biodiversity by supporting the long-term persistence of viable, natural populations of wild species. Conservation practice has long been guided by genetic, ecological and demographic indicators of risk. Emerging evidence of animal culture across diverse taxa and its role as a driver of evolutionary diversification, population structure and demographic processes may be essential for augmenting these conventional conservation approaches and decision-making. Animal culture was the focus of a ground-breaking resolution under the Convention on the Conservation of Migratory Species of Wild Animals (CMS), an international treaty operating under the UN Environment Programme. Here, we synthesize existing evidence to demonstrate how social learning and animal culture interact with processes important to conservation management. Specifically, we explore how social learning might influence population viability and be an important resource in response to anthropogenic change, and provide examples of how it can result in phenotypically distinct units with different, socially learnt behavioural strategies. While identifying culture and social learning can be challenging, indirect identification and parsimonious inferences may be informative. Finally, we identify relevant methodologies and provide a framework for viewing behavioural data through a cultural lens which might provide new insights for conservation management.